The History of Emotions and Middle English Literature. Issue 6 (June 2016) - Downes, Stephanie; McNamara, Rebecca F.
Abstract: Critics have long addressed questions of affect, feeling and emotional expression in Middle English literature, but only in recent years has their interest begun to take theoretical form under the rubric of the 'history of emotions'. Current critical attitudes to the study of emotions in the past have been shaped substantially by the work of historians, whose focus on emotion in documentary sources has been influenced in turn by research in the fields of sociology, anthropology, psychology, linguistics and, increasingly, the cognitive sciences. How might existing methodologies situating emotions historically drive new approaches in Middle English literary studies? This article contends that existing analyses of Middle English literature relating to affective discourses might fruitfully be brought into conversation with new multidisciplinary forms of research into past emotions. We survey current critical trends in both the history of emotions and in Middle English literature. Case studies of two late Middle English literary texts, the anonymous Sir Orfeo and Geoffrey Chaucer's Troilus and Criseyde, show how the last fifty years of scholarship has addressed emotions in Middle English literature. We conclude by suggesting future directions that might be taken up by critics of medieval English literary texts and genres to develop further the relationship between literary studies and the history of emotions.